A cross-sectional study on the prevalence, knowledge, attitude and practice of alcohol consumption among the population aged 13 years and above in longhouses Johnnie, Langgie and Hamdam, Kampung Sare, Sarikei from 14 February 2009 to 3 April 2009 - Loong, Tonnii Sia Loong; Han, Chia Lip; Yee, Chong Fui; Izmizah, bte Yusof; Seong, Loh Chee; Chuong, Mark Wong Ngie; Mohd Fakhrulsani, b Abdul Hamid; Mohd Ridzwan, b Esmon; Nurul Ain, bt Mohamed Ashrudin; Yi, Ooi Shin; Praveenna, Nagaratnam; Rahimah, bt Abdul Razak; et al. (Universiti Malaysia Sarawak (UNIMAS), 2009)
In Malaysia, prevalence of binge drinking is more than 30% and is more common in rural area. No known available data regarding the prevalence, knowledge, attitude and practice of alcohol consumption among the population aged 13 years and above in Kampung Sare, Sarikei.